SKOPOS THEORY IN THE LIGHT OF FUNCTIONAL TRANSLATION - Iryna V. Nedainova (Alfred Nobel University Journal of Philology, 2021)
Today, the transfer of as much information as possible as quickly as possible is becoming the norm, with the accelerating development of the modern world, the social function of translation as an activity is also changing. At this time, the degree of the translation unit adequacy is under challenge. The postulate of the adequacy of translation known to all professionals in the field of translation, according to which every author's message should be translated as close to its meaning as possible and must accentuate its content, is taking a back seat. Skopos theory in 1978 authored by the German linguist and translator H. Vermeer pushed a reconceptualization of translation activity where the goal (skopos) conforming to which a translation piece is made and the function determined by the addressee are focused. The revolutionary idea of this theory lies in the fact that it decrowns the dominance of the source text and emphasizes the role of the translator as the creator of the translation text, giving priority to the skopos that was set to create this translation, and bringing the customer out of the shadow of the translation. The main ideas of this theory as well as the interest that is actively shown in foreign translation studies determine the urgency of this research. This article presents arguments for the foundations of this theory that may be used to reproduce modern functional translation, in particular in the scientific and technical field. The purpose of our investigation is to form specific procedures for translation activities in order to reproduce high-quality narrowly specialized translation from the perspective of the target direction of translation activities according to Skopos theory. A scientific and technical text, in terms of its functional characteristics, is best suited for the Skopos theory adaptation. Based on the study of this theory’s foundations, we tried to create some recommendations for translators that may be of interest for the development of specific procedures for the translation of scientific and technical texts. The methodology of comparing the generally accepted theory of adequacy and Skopos-theory makes it possible to identify those attractive features of the latter that add to the creation of high-quality translation text, which indicates the current direction of this work in the field of the Ukrainian scientific and technical translation studies. The given research includes general logical and general scientific methods such as analysis and synthesis, induction and deduction, descriptive and comparative methods to render our own conclusions regarding the analyzed theory. In the course of our research, it became possible to determine the paradigm of the main provisions of Skopos theory, which can guide scientific and technical translators in their activity, and on the basis of these provisions’ study to reproduce certain recommendations for professional translators regarding the translation of scientific and technical texts The overall intention of the paper was not to dictate mandatory rules to be followed by a translator, but rather to explain a new methodological approach and to form some appropriate techniques that can teach specialists in scientific and technical translation to evaluate their work as well as to take responsibility for a final translation product in face of both, the customer of the translation and the audience for which this translation is intended.